Biodiversity and technological potential of the Weissella strains isolated from different regions producing artisanal cheeses in Brazil - Teixeira, Camila Gonçalves (2018)
The genus Weissella is composed of bacteria belonging to the group known as lactic acid bacteria (LAB), therefore it is capable of producing lactic acid through the fermentation of carbohydrates. Bacteria of this genus are autochthonous to both dairy and non-dairy environments and many strains have the ability to produce various compounds of interest to the food industry, such as exopolysaccharides, bacteriocins and hydrogen peroxide, for example. This work began with the study of the biodiversity of Weissella strains isolated in the regions producing artisanal cheeses in Brazil. For this, the analyzes of PFGE and Rep-PCR were carried out, which allowed to group the studied strains. With these analyzes it was observed that each study region represents a specific ecological niche and in addition it was also observed that the PFGE technique makes it possible to obtain a better result of heterogeneity between the strains of the same species. After selecting the representatives of each group the antimicrobial potential of these strains was analyzed through antagonistic analyzes and bacteriocin production against the pathogens Listeria monocytogenes ATCC 15313, Staphylococcus aureus subsp. aureus ATCC 6538, Salmonella enterica ATCC 14028 and Escherichia coli ATCC 11229. The results obtained showed that most of the isolates tested showed good inhibition of the pathogens, with inhibition percentage higher than 60% in the antagonism test and with a decrease in the pH of the medium after 24 h of incubation due to acid production. However, there was no significant inhibition of pathogens when the bacteriocin production test was performed. After the study related to the antimicrobial potential of the strains of Weissella, the technological potential of these cultures was evaluated aiming to characterize phenotypically and to direct its potential of application in the dairy industry. Thirteen strains were selected at a similarity level of 72% in PFGE and 10% (w/v) reconstituted skim milk were tested to determine coagulation capacity, diacetyl production, exopolysaccharide production, acidification capacity, extracellular proteolytic activity and characteristics of the clot formed. As a result, some strains showed positive results for most of the tests performed, except for the exopolysaccharide production, highlighting the strain number 16 isolated from cheese of the southern of Pará, showing good acidification capacity and pH decrease of milk, and positive results for the tests of diacetyl production, proteolytic activity and homogeneous clot formation. As a conclusion, this work allowed us to understand the diversity of Weissella species found in the different regions producing artisanal cheeses in Brazil and how they are distributed in these environments, besides helping to understand the role of these strains in artisanal cheeses. It also showed that some of them have a favorable technological potential for future uses in the food industry as starter cultures and for the study of cheese defect prevention.